Well-Being of Renters in Ankara: An Empirical Analysis - Sarıoğlu-Erdoğdu, G. Pelin (Elsevier, 2015)
The body of literature on residential satisfaction has been growing not only in housing studies, but also in numerous other disciplines like urban planning, sociology and demographic studies. The absence of social housing, the high ratio of owner-occupation and the availability of good quality private rental stock in Turkey makes it a unique case for studies of residential satisfaction. This paper attempts to highlight the position of renters in Ankara as a specific group, arguing that the good physical attributes of the rental housing stock in Turkey serves for the “well-being” of renters, in contrast to the negative perceptions of renting presented in Western housing literature. The empirical part of the study reveals that physically the stock is not significantly differentiated with reference to tenure types. Furthermore, the social statuses of the tenants and owners are somewhat similar, meaning that the two population groups are not separated in the urban area. The results of the regression analysis reveal that “income” and “tenure type” are positive predictors of the well-being of households in Ankara, and much of this can be attributed to the decent quality of the Turkish stock. As long as there are no significant problems in their dwellings, renters tend to consider themselves as satisfied.
Keywords: Well-Being; Residential Satisfaction; Private Renting; Regression; Ankara-Turkey